Environmental Implications of Municipal Dump Site on Soil Nitrogen in Calabar Metropolis, Nigeria - Ediene, Victoria Francis; Akeh, Linus Beba; Iren, Otobong Benjamin; Afu, Sunday Marcus; Aki, Ene Emmanuel; Olim, Denis Michael (Richtmann Publishing, 2021)
Organic matter exhibit strong variations in nitrogen retention and transformation cycle in soil. However, nitrogen could be altered by seasonal variations, leading us to hypothesize that the open municipal waste dump site in Calabar exposed to dry and wet season could alter nitrogen dynamics in that soil. A total of sixty (60) composite soil samples were collected at different landscape positions (summit crest, shoulder slope, toe slope, interfluve slope, valley floor) of a municipal dump site and a control (no refuse area) during the dry and wet seasons in Calabar and analyzed to ascertain the effects on forms and status of soil nitrogen. The soils were loamy sand across the study location with pH values of 4.50, 7.00, 6.70, 7.30, 5.00, 7.30 (dry season) and 5.00. 7.30, 7.00, 7.40, 5.90, 7.40 (wet season) for the control, summit crest, shoulder slope, toe slope, interfluve slope and valley floor accordingly. Values obtained for total nitrogen (N) from the study site were generally low (<0.21 %), with values for dry season slightly higher than the wet season. NH4+ recorded higher content in wet than in dry season with values ranging between 12.11-14.11 mg/kg (control), 14.60 - 15.90 mg/kg (Summit crest); 18.25 - 20.05 mg/kg (Shoulder slope), 18.30 - 20.20 mg/kg (Toe slope), 12.30 - 14.00 mg/kg (Interfluve slope) and 9.24 -11.07 mg/kg (Valley floor). The Shoulder and toe slopes recorded the highest NH4+ concentration in the wet season. N02- contents documented for the control site were within the ranges of 2.78- 3.20 and 3.22-3.62 mg/kg while the dumpsite had values between 2.49-3.45 and 2.98 -3.22 mg/kg was observed for the shoulder position, the toe slope contained between 2.30-2.75 and 2.70 -2.82 mg/kg, the inter fluve slope had similar ranges of 2.32-2.90 and 2.70-3.08 mg/kg, and the valley floor 2.45-2.60 and 2.78-2.98 mg/kg. N02- values were higher for the wet than dry season. NO3- nitrogen was observed to be excessive across the dumpsite with the highest values > 80 mg/kg obtained at the valley floor. The NO3- values were higher in dry season across the all the landscape positions than in the wet season. The values were equally higher for the dumpsite than the control. It was observed that the dumpsite soils contend excessive NO3- which could be converted to nitrous oxide (N2O) thus contributing to green house (GHG) emissions. It was also noted that seasonal variation did not significantly affect the N content at the different landscape positions of the municipal dumpsite in Calabar. It is highly recommended that municipal waste be sorted and the organic materials composted to harness the rich NO3- content as observed in this research. Received: 22 September 2021 / Accepted: 25 October 2021 / Published: 5 November 2021